On the Existence of Global Weak Solutions for a Weakly Dissipative Hyperelastic Rod Wave Equation. (1st September 2014) - Yan, Haibo; Yong, Ls; Yang, Yu; Wang, Yang
Abstract : Assuming that the initial value v 0 ( x ) belongs to the space H 1 ( R ), we prove the existence of global weak solutions for a weakly dissipative hyperelastic rod wave equation in the space C ( [ 0, ∞ ) × R ) ⋂ ‍ L ∞ ( [ 0, ∞ ) ; H 1 ( R ) ) . The limit of the viscous approximation for the equation is used to establish the existence.